Analyzing Constraints in Conflict Management in Wasteland Development Project - M. Ullas , V. L. Madhu Prasad; G. R. Pennobaliswamy (Indian Journal of Extension Education, 2015)
The study was aimed to analyze the constraints encountered by Pragathi Bandu Self Help Group (SHG) members while implementing the Wasteland Development project. The present study was conducted in purposively selected Shimoga district of Karnataka state during 2013. Two taluks namely Shimoga and Bhadravathi were selected. From each taluk the villages having maximum number of Pragathi Bandu SHG members were selected. Total 36 Pragathi Bandu SHGs formed by SKDRDP were considered for the study. From each SHG, three members were randomly selected thus, making a total sample size of 108. The results revealed that all Pragathi Bandu SHG members expressed political influence, was major problem in resolving conflicts and majority (90.7%) of the respondents suggested to create general awareness about the essentiality of formation of SHGs for wasteland development activities.